On the art in the ancient Near East - Winter, Irene. (Culture and History of the Ancient Near East, 2009)
This second volume of collected essays, complement to volume one, focuses upon the art and culture of the third millennium B.C.E. in ancient Mesopotamia. Stress is upon the ability of free-standing sculpture and public monuments not only to reflect cultural attitudes, but to affect a viewing audience. Using Sumerian and Akkadian texts as well as works, the power of visual experience is pursued toward an understanding not only of the monuments but of their times and our own. \'These beautifully produced volumes bring together essays written over a 35-year period, creating a whole that is much more than the sum of its parts...No library should be without this impressive collection.\' J.C. Exum